COVID-19 in children in Odisha state, India: a retrospective review - Sanghamitra Pati; Girish Chandra Dash; Subhra Subhadra; Jyotirmayee Turuk; Debaprasad Parai; Usha Kiran Rout; Sonalika Rath; Jyotsnamayee Sabat; Rashmi Ranjan Nanda; Hari Ram Choudhary; Debdutta Bhattacharya (BMJ Publishing Group, 2021)
We retrospectively analysed the swab samples tested for COVID-19 from 7 March 2020 to 17 August 2021 at the Indian Council of Medical Research-Regional Medical Research Centre, Bhubaneswar, Odisha. 553 763 nasopharyngeal swabs were collected from individuals suspected with COVID-19 in Odisha state. 75 190 (13.6%) samples were positive by reverse transcription-PCR. There were 5988 (8%) cases in children and young people under 18 years old. Odisha reported 996 153 COVID-19 cases which resulted in 6985 deaths in adults and 36 in children and young people under 18 years old.